Acanthosis nigricans and insulin resistance in obese children - Kristellina Sangirta Tirtamulia; Adrian Umboh; Sarah Maria Warouw; Vivekenanda Pateda; Frecillia Regina (Indonesian Pediatric Society, 2010)
Background Acanthosis nigricans (AN) is a skin condition characterized by darkening and thickening of skin. AN has been reported to be linked to insulin resistance (IR), that associated with type 2 diabetes, in obese children in many country.Objective To determine the relation between acanthosis nigricans and insulin resistance in obese children.Methods We conducted a cross sectional study in Wenang District, Manado, from October 2009 until January 2010. We examined 54 obese children aged 10-14 Â years for insulin resistance using Homeostasis Model Assessment of Insulin Resistance Index (HOMA-IR). We analyzed the results byT-test and phi coefficient correlation. The value of P<O.05 was significant in statistical analysis.Results Acanthosis nigricans was positive in 33 children. Insulin resistance was found in 34 from 54 subjects, 28 of them has AN and 6has no AN. Obese children with AN had higher HOMA-IR than children without AN. Presence of AN was associated with IR (P<O.OOl, r=0.57).Conclusions There is a weak correlation between AN and IR in obese children. It is important to identify obese children with IR for early intervention and prevention of type Â 2 diabetes, but AN could not be a reliable marker of IR.